(untitled) (Scientific journal of the Fergana State University, 2024)
In the article suggested ways of increasing effective study practice and practical skills of students. Educational practice as an organic part of the educational process, providing a mix of theoretical preparation of students with their practical activities, is one of the means of successful preparation of students for work. It provides an opportunity to fully understand the patterns and principles of education, to master professional skills and experience of practical work. The educational activity of students should be organized as a process of solving scientific and practical problems that allow each student to carry out self-development, self-knowledge, self-realization. With this approach, the main subject in the college practice is the student. It ceases to be a store of knowledge with normalized reactions: to present data about the college, about the teacher, about the students, to conduct and analyze so many lessons and extracurricular activities. The key is the decision of the student of pedagogical problems in the conditions of college, since the main thing is the pupil himself, changes in his experience, the formation of his professional competence\